Faktor-Faktor Penghambat Minat Siswa Kelas X Pada Pembelajaran Seni Budaya (Tari) Di SMK Negeri 9 Padang - Quinta Dianda Voneline; Susmiarti Susmiarti; Indrayuda Indrayuda (SENDRATASIK UNP, 2021)
This study aims to describe the factors inhibiting the interest of class X students in learning cultural arts (dance) at SMK Negeri 9 Padang where students are less inclined in learning cultural arts (dance) and do not have a good response, because this research focuses on the problem of student interest in learning cultural arts (dance). This type of research is qualitative research with descriptive methods. The research objects were students of class X Ph4 and the arts and culture teachers of SMK Negeri 9 Padang. The instruments in this study were the researchers themselves and the researchers were assisted by instruments such as writing instruments, cellphones, and laptops. The technique of collecting data results by means of interviews, observation and documentation. Data were analyzed using steps, namely data reduction, data collection, verification and conclusions. The results of the research in class X Ph4 showed that the inhibiting factors of interest in learning were influenced by students' lack of attention in the learning process, then the attitude of students who were not polite to the teacher when explaining dance learning. Interest in learning is also influenced by the talents of students, in learning dance talent is very supportive of success in imitating dance movements. Students who have talent will tend to listen to the material well then students who have a sense of pleasure in learning will respond to the material optimally. Students' motivation is very lacking in learning dance as a result, students are reluctant to take part in learning dance practices, only some students want to take part in learning.